Evaluating of the Relationships between aAverage Particle Size and Microstructure-Mechanical Properties of Materials Produced in Different Compositions using Ultrasonic Method - V. Özkan Bilici; A. Yönetken (Archives of Metallurgy and Materials)
Pulse-echo ultrasonic test, which is one of the non-destructive testing methods, was used to measure ultrasonic quantities such as longitudinal velocity (VL), shear velocity (VT) and attenuation coefficient (α) in FeCrMn composites. The corresponding elastic constants were determined depending on the longitudinal and transverse velocity. The aim was to reveal the correlation between the microstructural and mechanical properties of FeCrMn composites and ultrasonic quantities. The effect of adding Cr particles on VL and VT velocities is obviously attributed to the change in elastic and shear modulus of FeCrMn composites. It was found that both VL and VT velocities, Young’s modulus (E) and shear modulus (G), as well as hardness values, changed approximately linearly with increasing Cr content. In this study, samples with different volumetric compositions were produced using the powder metallurgy method. It has been revealed that both the applied method and the increase in the amount of Cr have a significant effect on the velocities of VL and VT. The increase in VL and VT is due to the increase of Cr particles, the homogeneous distribution of Cr, the formation of samples especially at a certain temperature, and the decrease of porosity. As a result of these, a decrease in attenuation values was observed depending on the mean grain size. Elastic constants were found to vary in the same way as ultrasonic velocities. By increasing the Cr content both the hardness values and the shear modulus were improved and a good correlation was observed with the grain size.